A model for investment planning in Mexico - Zelaya de la Parra, Eduardo (Estudios Económicos de El Colegio de México, 1993)
This paper presents a model for the selection of investment projects and the optimal way to finance them. This is done using Mixed Integer Programming and Monte Carlo risk simulation. The objective is the maximization of the value of the firm given the constraints imposed by liquidity, debt ceilings, and the Mexican tax structure.